CAN PRICE LIMITS REDUCE STOCK PRICE VOLATILITY? EMPIRICAL EVIDENCE FROM AMMAN STOCK EXCHANGE - Haddad, Dima (2007)
Following the October 1987 stock market collapse, interest in the effect and impact of circuit breakers on market volatility has grown among practitioners, academics and regulators.